High T-helper-1 cytokines but low T-helper-3 cytokines, inflammatory cytokines and chemokines in children with high risk of developing type 1 diabetes - Stechova, Katerina; Bohmova, Kristyna; Vrabelova, Zuzana; Sepa, Annelie; Stadlerova, Gabriela; Zacharovova, Klara; Faresjö, Maria (Diabetes/metabolism research and reviews, 2007)
BACKGROUND: Type 1 diabetes (T1D) is suggested to be of T-helper (Th)1-like origin. However, recent reports indicate a diminished interferon (IFN)-gamma secretion at the onset of the disease. We hypothesize that there is a discrepancy in subsets of Th-cells between children with a high risk of developing T1D, children newly diagnosed with T1D and healthy children. METHODS: Peripheral blood mononuclear cells (PBMC) were collected from children at high risk for T1D (islet cells antibodies [ICA] >/= 20 IJDF-U), those newly diagnosed and healthy children carrying the HLA-risk gene DQB1*0302 or DQB1*0201 and DQA1*0501. Th1- (IFN-gamma, tumour necrosis factor [TNF]-beta, interleukin [IL]-2), Th2- (IL-4,-5,-13), Th3- (transforming growth factor [TGF-beta], IL-10) and inflammatory associated cytokines (TNF-alpha, IL-1alpha,-6) and chemokines (monocyte chemoattractant protein [MCP]-1,-2,-3, Monokine unregulated by IFN-gamma [MIG], Regulated on Activation, Normal T-cell Expressed and Secreted [RANTES], IL-7,-8,-15) were detected in cell-culture supernatants of PBMC, stimulated with glutamic acid decarboxylase 65 (GAD(65)) and phytohaemagglutinin (PHA), by protein micro array and enzyme linked immunospot (ELISPOT) technique. RESULTS: The Th1 cytokines IFN-gamma and TNF-beta, secreted both spontaneously and by GAD(65)- and mitogen stimulation, were seen to a higher extent in high-risk children than in children newly diagnosed with T1D. In contrast, TNF-alpha and IL-6, classified as inflammatory cytokines, the chemokines RANTES, MCP-1 and IL-7 as well as the Th3 cytokines TGF-beta and IL-10 were elevated in T1D children compared to high-risk children. CONCLUSION: High Th-1 cytokines were observed in children with high risk of developing TID, whereas in children newly diagnosed with T1D Th3 cytokines, inflammatory cytokines and chemokines were increased. Thus, an inverse relation between Th1-like cells and markers of inflammation was shown between children with high risk and those newly diagnosed with T1D.
Keywords: chemokiny; Th1 buňky; Humans; dítě; C-Peptide; Child; cytokiny; Female; C-peptid; lidé; Biomarkers; mladiství; diabetes mellitus 1. typu; biologické markery; ženské pohlaví; Male; Adolescent; genetická predispozice k nemoci; Genetic Predisposition to Disease; Cytokines; Th1 Cells; regulační T-lymfocyty; T-Lymphocytes, Regulatory; Inflammation Mediators; mužské pohlaví; mediátory zánětu; Diabetes Mellitus, Type 1; Chemokines